Determination of moisture sorption isotherm of peanut cake - Endoma, Helen Anievas; Galvez, Flor Crisanta F. (2001., 2001)
The study was conducted to determine the moisture sorption isotherm of peanut cake at room temperature. The method of Lang was used to assess the equilibrium moisture content of peanut cake samples exposed to different relative humidities. The moisture content of peanut cake was determined using a vacuum-oven, the value obtained (2.2%) was used in the calculation of equilibrium moisture content. Dtermination of initial water activity ((Aw = 0.39)) of the sample was done using a water activity meter. The value obtained using the water activity meter was found to agree with the value obtained using the moisture isotherm plot. A complete moisture sorption isotherm was obtained for peanut cake. The different regions in the isotherm were assigned on the basis if varying slopes of curves obtain in the graph and more directly using the local Isotherm method. From the results of calculation using the BET equation, it was determined that the monolayer value for the peanut cake sample was 1.02g water per 100g dry solid. On the other hand, using the Local Isotherm Method, the boundary between Zones I and II was found to occur at Aw=0.34 and between Zones II and III at 0.72.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut products; Cake